KUALITAS PERAIRAN LAUT DESA JIKUMERASA KABUPATEN BURU BERDASARKAN PARAMETER FISIK, KIMIA DAN BIOLOGI - Umasugi, Samsia; Ismail, Irwan; Irsan, Irsan (Program Studi Pendidikan Biologi FKIP Unpatti, 2021)
Background: Jikumerasa waters are one of the waters that have ecological and economic value. The high level of human activity in utilizing marine waters in Jikurasa Village has the potential to cause pollution and reduce water quality. For this reason, it is necessary to measure the water quality of Jikuemerasa Village based on the conditions of physical, chemical and biological parameters.Methods: This research was conducted from September 2021 to October 2021. Sampling was carried out at seven stations. measurement of physical and chemical parameters directly (in situ), namely: temperature, brightness, pH and salinity. Water samples were taken to measure physical, chemical and biological parameters ex situ including: DO, BOD, COD and coliform bacteria in the laboratory.Results: The study showed that the parameters that were still in accordance with the quality standards at all research stations were: temperature, brightness, COD, BOD, Pb metal and the number of coliform bacteria. For the salinity parameter, only station IV has a salinity below the quality standard. In the DO parameter, there are several research stations (stations I, IV and VI) which are still in accordance with the quality standard, while the other stations are below the quality standard. Parameters that do not match the quality standards are: TDS and pH.Conclusion: The condition of the quality of the marine waters of Jikumerasa Village, Buru Regency based on physical, chemical and biological parameters, mostly still meets the specified quality standards.